KOMUNIKASI TRANSENDENTAL DALAM RITUAL PARISUDHA VAYU DI PASRAMAN KAYU MANIS LATA MAHOSADHI DESA TEGALMENGKEB TABANAN - Putu Mia Kusuma Dew; I Wayan Wastawa; Ni Made Yulian (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
An interesting phenomenon at this time in Bali, Hinduism begin to make rituals of cleansing themselves not only as a spiritual activity but also as a life style. This study aims to one of them is the Parisudha vayu ritual, which means cleansing oneself by the wind power of Lord Vayu and is a method of activating oneself to connect with the energy of the universe. A sacred knowledge of Balinese ancestors stored in the natural silence of the village of Tegalmengkeb. This study focuses on the discussion of The process of transcendental communication in the implementation of the Parisudha vayu ritual at Pasraman Kayu Manis Lata mahosadhiforms of transcendental communication in the implementation of the Parisudha vayu ritual at Pasraman Kayu Manis Lata mahosadhi. The research objective is to develop transcendental communication in society. The results of this study indicate several things. First, ). the transcendental communication process goes through 3 stages in the parisudha vayu ritual, including: the preparation stage, namely establishing oneself and preparing the activation equipment, the implementation stage, namely the process of purifying the hands (karosodhana), the bhuwana chakra mudra movement and the activation of parisudha vayu and the final stage of giving three passwords. for the implementation of the next ritual. Second, the form of transcendental communication in the Parisudha vayu ritual is divided into two, namely verbal communication patterns (meaning in prayer in Parisudha vayu ritual) and nonverbal communication patterns (meaning in each movement in the Parisudha vayu ritual), respectively. -Each people practice. It is at this point that the private area of transcendental communication in the parisudha vayu ritual occurs (communication between humans and God. Third, the impact that is felt on Hindu religious life, Hindu community life and Hindu community life.